Educational needs of the primary education teachers in inclusive education of the pupils from socially disadvantaged backgrounds in Slovakia - Rochovská, Ivana; Kušnírová,, Veronika; Kolibová, Daniela; Dolinská, Eva; Dudek, Mieczyslaw (Special Education, 2020)
The study presents the results of the research examining the educational needs of the teachers and their interest about the themes of courses and educational programmes in connection with actual needs arising from changes in the Slovak education system due to the gradual promotion of inclusion. The main research method was the questionnaire aimed at detection of primary level teachers’ needs for the professional development and trainings, the identification of primary education teachers’ needs for successful implementation of inclusion in the learning of the pupils from socially disadvantaged backgrounds. This study presents if there exist statistically significant differences in self-reflexive perception of the need to improve in topics related to the implementation of inclusive education and the characteristics of respondents (age, length of the teaching practice, willingness to grow personally and to educate).
Keywords: educational needs; inclusion; further education of teachers